التكنولوجيا الزراعية ودورها في حل أزمة الغذاء العالمية - قطاف، سهيلة (University of Eloued جامعة الوادي, 2025)
تهدف هذه الورقة البحثية إلى دراسة التكنولوجيا الزراعية وكيف لها أن تشكل أداة استراتيجية لحل أزمة الغذاء العالمية، بالاعتماد على المنهج الوصفي التحليلي، من خلال التطرق أولا إلى أدبيات الدراسة والمتعلقة بأزمة الغذاء والتكنولوجيا الزراعية، ثم التطرق إلى دور التكنولوجيا في تحسين الإنتاج وكذا دور هذه التكنولوجيا على أبعاد الأمن الغذائي، ثم تم عرض بعض التجارب الدولية التي تبنت هذا النوع من التكنولوجيا. وقد تم التوصل من خلال التجارب الدولية أن التكنولوجيا الزراعية تمثل ركيزة أساسية في مواجهة أزمة الغذاء العالمية من خلال رفع الإنتاجية وتقليل الهدر في الموارد. فقد ساهمت الزراعة الذكية مناخيا والري بالتنقيط والاستشعار عن بعد في تحسين كفاءة استخدام المياه والتربة. كما أدت الرقمنة الزراعية إلى تعزيز الأمن الغذائي، وتؤكد النتائج أن الاستثمار في الابتكار الزراعي هو السبيل الأنجع لتحقيق استدامة الإنتاج وضمان توافر الغذاء عالميا. This research paper aims to study agricultural technology and how it can serve as a strategic tool to address the global food crisis, relying on the descriptive-analytical approach. It first explores the literature related to the food crisis and agricultural technology, then examines the role of technology in improving production as well as its impact on the dimensions of food security. The paper also presents some international experiences that have adopted this type of technology. Findings from these international experiences reveal that agricultural technology constitutes a fundamental pillar in addressing the global food crisis by increasing productivity and reducing resource waste. Climate-smart agriculture, drip irrigation, and remote sensing have contributed to improving the efficiency of water and soil use. Moreover, digital agriculture has enhanced food security, and the results confirm that investment in agricultural innovation is the most effective path to achieving sustainable production and ensuring global food availability.
Agricultural technology and its role in solving the global food crisis
مقال
Keywords: أزمة غذاء; تكنولوجيا زراعية; الأمن الغذائي; زراعة مبتكرة; Food Crisis; Agricultural Technology; Food Security; Innovative Agriculture